Consumer Protection in Andhra Pradesh (A Case Study of Hyderabad District Consumer Voluntary Organizations and Consumer Redressal forums) - Purushotam Rao, P.; Parveen, S. (Indian Journal of Marketing, 2004)
Consumerism in India is beginning to establish an identity of its own. As ours is a developing country facing problems like illiteracy, poverty and unemployment, people can be exploited very easily by the self motivated private manufacturers and corrupt public officials. They are exploiting the consumers because of their ignorance of their consumer rights. Though they are aware of their rights, they are unable to get justice through courts, which are known for their delay, very completive nature of rules, regulations and expansiveness. In these circumstances the consumer protection has acquired immense importance. The purpose of the study is to analyze the role played by the consumer protection agencies and to suggest measures.